The Effect of Organisational Structure on the Effective Management of the Ministry Of Defence - Oklu, E.M. (University of Ghana, 2019)
This study seeks to examine how organisational structure affects organisational effectiveness at the Ministry of Defence. The study employed the qualitative research methodology where senior management staff comprising civil servants and military officers on attachment from the Ghana Armed Forces were interviewed. The use of semi-structured interviews were employed to collect data from twelve (12) senior staff members of the Ministry. The findings from the study revealed that the organisational structure at the Ministry is hierarchical. Also, regarding how the organisational structure affects organisational effectiveness, the findings revealed that duties and responsivities are not well allocated and reporting lines in some cases were not clear. Integration of the military into the structure was also not effective and this was affecting organisational effectiveness. Further to this, findings revealed that there were bottlenecks in the current structure of the ministry, some of the bottlenecks identified are miscommunication, slow information flow, undefined roles, poor communication and an unfavourable environment for meeting critical deadlines as the bottlenecks. The study recommends that the validation and dissemination of the organisational manual must be undertaken, to ensure employee engagement and involvement. Management of the Ministry must also be flexible in the design and implementation of organisational structure to reduce bureaucracies, increase creativity and ensure timely delivery of task. There was also the need to improve communication flow within the Ministry ensuring that there was a sense of camaraderie and shared vision.
MA. Management and Administration
Keywords: Organisational Structure; Ministry of Defence